2020
DOI: 10.1038/s41589-020-00659-5
|View full text |Cite
|
Sign up to set email alerts
|

Selective regulation of human TRAAK channels by biologically active phospholipids

Abstract: TRAAK is an ion channel from the two-pore domain potassium (K 2P ) channel family with roles in maintaining the resting membrane potential and fast action potential conduction. Regulated by a wide range of physical and chemical stimuli, the affinity and selectivity of K 2P 4.1 towards lipids remains poorly understood. Here we show the two isoforms of K 2P 4.1 have distinct binding preferences for lipids dependent on acyl chain length and posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 61 publications
1
43
0
Order By: Relevance
“…Cholesterol Activity regulation [8,9] Activity and changes in conformation [10], Modulation of substrate binding affinity [11] Channel inhibition [12] Activation [13], Signalling [14,15], Stability [16,17], Allosteric regulation [18], Lower affinity ligand binding [17], Oligomerisation [19][20][21][22][23] PA Activity [24] Stabilisation [25] PE Dimer formation and function [26], Dimer formation [27], conformer stability [28] Conformer stabilisation and channel desensitisation [29] Agonist and antagonist binding affinities [30], Increase G protein coupling [31,32] Protein assembly [33] PC Dimerisation [34], β-arrestin interaction and function [35], Increase G protein coupling [31] PG Oligomerisation and function [36] Conformer stabilisation and channel desensitisation [37] Increase G protein coupling [30,38], Active conformer stability [39], β-arrestin interaction and function [35], Decrease G protein coupling [31] PS Dimer formation [27], Stabilisation [25], Dimerisation [34], Decrease G protein coupling [31] PI Dimer formation and function…”
Section: Lipid Entitymentioning
confidence: 99%
See 1 more Smart Citation
“…Cholesterol Activity regulation [8,9] Activity and changes in conformation [10], Modulation of substrate binding affinity [11] Channel inhibition [12] Activation [13], Signalling [14,15], Stability [16,17], Allosteric regulation [18], Lower affinity ligand binding [17], Oligomerisation [19][20][21][22][23] PA Activity [24] Stabilisation [25] PE Dimer formation and function [26], Dimer formation [27], conformer stability [28] Conformer stabilisation and channel desensitisation [29] Agonist and antagonist binding affinities [30], Increase G protein coupling [31,32] Protein assembly [33] PC Dimerisation [34], β-arrestin interaction and function [35], Increase G protein coupling [31] PG Oligomerisation and function [36] Conformer stabilisation and channel desensitisation [37] Increase G protein coupling [30,38], Active conformer stability [39], β-arrestin interaction and function [35], Decrease G protein coupling [31] PS Dimer formation [27], Stabilisation [25], Dimerisation [34], Decrease G protein coupling [31] PI Dimer formation and function…”
Section: Lipid Entitymentioning
confidence: 99%
“…A recent study on the two-protein domain potassium (K 2P ) channel, TRAAK, using a combination of native MS and liposome-based potassium efflux assay, allowed a detailed analysis of the lipids involved in the regulation of channel activity. The results revealed that TRAAK was activated by high affinity binding of phosphatidic acid (PA) [24].…”
Section: Channelsmentioning
confidence: 99%
“…This suggests that CsA binding primes the transporter for subsequent lipid binding, either through a conformational change or adaptation of the ligand pocket. Such a method was used successfully on GPCRs [ 132 ], channels [ 133 , 134 , 135 , 136 ], transporters [ 131 , 137 , 138 , 139 ] and other IMPs [ 140 ], highlighting the role of specific lipid species in allosteric coupling.…”
Section: Lipids As Modulators Of Ligand Bindingmentioning
confidence: 99%
“…These lipids have been previously suggested to activate multiple K + channels such as K ir , TREK1 and TRAAK. 79 , 80 , 81 …”
Section: Roles For Other Anionic Phospholipids and Cholesterol In Modulating Ion Channel Activitymentioning
confidence: 99%
“… 121 , 122 Early nMS work on ion channel lipid interactions focused on the effect of lipids (and other effects) on the stoichiometry of the mechanosensitive channel of large conductance (MscL) in different bacteria. 121 Furthermore, nMS has been applied to characterise the selectivity of lipid binding to the isoforms of the TRAAK channel 80 and to K ir 3.2 where PIP 2 was shown to bind selectively and single mutations influence the affinities and specificity. 124 A more comprehensive review on characterising protein-lipid interactions through nMS can be found in.…”
Section: Experimental Affinity Gating and Efficacy Of Lipidsmentioning
confidence: 99%